Digital Cognitive Behavioral Therapy for the Average Person in Developing Countries - Muhammad Abdullah; Muhammad Yahya Saeed (Kashmir Journal of Science)
Digital Cognitive Behavioral Therapy (DCBT) is an effective treatment choice for Mental Health Conditions (MHC), particularly for those who face constraints in accessing traditional in-person therapy. However, in developing countries, several hindrances such as lack of technology, digital illiteracy, inadequate internet connectivity, and cultural barriers deter the average person from effectively using DCBT. The study examines and presents SWOT (Strengths, Weaknesses, Opportunities, and Threats) of several diverse types of online resources, including online counseling platforms, peer-to-peer support communities, self-help programs, mindfulness meditation resources, self-help therapy modules, videos, online therapy services for teenagers, mental health first aid resources, confidential and anonymous support services. The study presents a review of the most widely used and effective DCBT resources and it evaluates the difficulties faced by people in accessing these resources in Pakistan. The results reveal that only 5% of individuals seek in-person therapy often, with 68% having limited knowledge of online mental health resources. 77% of survey participants have never used online mental health resources and express concerns about privacy and security. Based on the findings and literature review the study guides the development of strategies to enhance access to DCBT resources.